2007
DOI: 10.1093/europace/eum149
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of automatic atrial overdrive pacing efficacy on reduction of paroxysmal atrial fibrillation

Abstract: We could not demonstrate a reduction of AF burden defined as cumulative time in AF by the AO algorithm, in patients who are paced for standard indications and PAF, neither from the RAA nor from the LAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…In contrast, a recent study found no decrease by the AOP algorithm on AF burden, defined as the cumulative time spent in mode switch, in patients paced for standard indications and paroxysmal AF, whether from the right atrial appendage or from the low atrial septum. 15 As shown in our study, the correlation between the rate of detecting AHRE and the upper pacing rate is a key factor with respect to RNRVAS induced by AOP. Most previous studies did not provide enough detailed information regarding the detected RNRVAS.…”
Section: Prevention Of Af By the Aop Algorithmsupporting
confidence: 51%
“…In contrast, a recent study found no decrease by the AOP algorithm on AF burden, defined as the cumulative time spent in mode switch, in patients paced for standard indications and paroxysmal AF, whether from the right atrial appendage or from the low atrial septum. 15 As shown in our study, the correlation between the rate of detecting AHRE and the upper pacing rate is a key factor with respect to RNRVAS induced by AOP. Most previous studies did not provide enough detailed information regarding the detected RNRVAS.…”
Section: Prevention Of Af By the Aop Algorithmsupporting
confidence: 51%
“…9,10 However larger trials were unable to confirm the initially positive results. 13,14 This difference can be explained by the 'mixed bag' of patients included in the larger trials who mostly had a short P-wave duration. Until now, atrial septum pacing could only be recommended in patients with a clearly prolonged P-wave duration (>120 msec), where shortening of the total atrial activation time is a clear component in the prevention of ATAs.…”
Section: Interruptive Pacing To Treat Atrial Fibrillationmentioning
confidence: 99%
“…[1][2][3][4][5][6] There is growing evidence to suggest that pacing at the atrial level in the region of Bachmann's bundle, the interatrial septum (IAS) or even multiple atrial sites may have advantages in patients with atrial fibrillation. [6][7][8][9][10] However, these specific site pacing techniques require extremely accurate lead positioning compared with those used for conventional bradycardia indications. 11 This may explain that adequate results have not yet been obtained with these new pacing approaches in a considerable number of patients.…”
Section: General Considerations: Specific Site Pacing Techniquesmentioning
confidence: 99%